2003
DOI: 10.1161/01.atv.0000074899.60898.fd
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Levels of Heat Shock Protein 70 Are Associated With Low Risk of Coronary Artery Disease

Abstract: Objective-Previous studies suggest that heat shock protein (HSP) 60 has a contributory role in atherosclerosis development. We examined whether circulating HSP70 protein and anti-HSP70 antibodies are associated with coronary artery disease (CAD). Methods and Results-Blood samples from 421 patients (62% men, mean age 57 years) evaluated for CAD by coronary angiography were tested. Serum HSP70 was detectable in 67% of study subjects with levels ranging from 0.2 to 27.1 ng/mL (mean, 1.08; median, 0.5). HSP70 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 31 publications
6
116
3
5
Order By: Relevance
“…A soluble heat-shock-mediated component to cardiovascular disease has been suggested by a number of studies. Previous works have shown an inverse correlation between circulating Hsp70 levels and atherosclerotic disease progression in cardiac (Zhu et al 2003;Zhang et al 2010) and in extracardiac vascular calcifications, such as peripheral artery disease of the lower extremities and carotid artery disease (Wright et al 2000;Martin-Ventura et al 2007). In their elegant study, Martin-Ventura et al (2007) showed significantly decreased Hsp70 levels in plasma of patients with CAD in relation to matched healthy subjects.…”
Section: Discussionmentioning
confidence: 95%
“…A soluble heat-shock-mediated component to cardiovascular disease has been suggested by a number of studies. Previous works have shown an inverse correlation between circulating Hsp70 levels and atherosclerotic disease progression in cardiac (Zhu et al 2003;Zhang et al 2010) and in extracardiac vascular calcifications, such as peripheral artery disease of the lower extremities and carotid artery disease (Wright et al 2000;Martin-Ventura et al 2007). In their elegant study, Martin-Ventura et al (2007) showed significantly decreased Hsp70 levels in plasma of patients with CAD in relation to matched healthy subjects.…”
Section: Discussionmentioning
confidence: 95%
“…[14][15][16][17] It has been reported that anti-Hsp-70 titres are not elevated in subjects with severe coronary atherosclerosis, whereas titres to Hsp-60 and -65 were significantly raised in these patients. 15,17 It has also been reported that patients with type 2 diabetes mellitus have significantly higher anti-Hsp titres compared with non-diabetic controls. 18 Current evidence suggests that antibody titres to Hsps are elevated in patients with vascular disease, and that this is related to the severity of atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…However, the connection between HSP70 or anti-HSP70 antibody levels and CVD or CVD risk phenotypes is unclear. Low serum levels of HSP70 has been associated with atherosclerosis in subjects with established hypertension [18] and coronary artery disease [19]. However, patients with intermittent claudication, critical lower limb ischaemia, aneurysms [20], hypertension [21] and cerebral ischemia [22] have elevated anti-HSP70 antibody levels.…”
Section: Discussionmentioning
confidence: 99%